1984
DOI: 10.3758/bf03198423
|View full text |Cite
|
Sign up to set email alerts
|

Memory for unattended events: Remembering with and without awareness

Abstract: The effects of memory for unattended events-for example, events that occur while a person is asleep, anesthetized, or selectively attending to other ongoing events, as in a speechshadowing task-are rarely revealed in tests of retention that require remembering to be deliberate or intentional. Might such effects become evident in tests that do not demand awareness of remembering? Results of the present shadowing study, involving the recognition and spelling of previously unattended homophones. suggest an affirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
215
4
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(236 citation statements)
references
References 27 publications
15
215
4
1
Order By: Relevance
“…By doing so, we extended results of earlier experiments (Eich, 1984;Koriat & Feuerstein, 1976) that have shown differential effects of attention on conscious recollection, in comparison with other uses of memory. Dividing attention influenced people's ability to consciously recollect having read a name, as measured by list recognition, but left in place effects of reading a name on its familiarity, as indexed by fame judgments.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…By doing so, we extended results of earlier experiments (Eich, 1984;Koriat & Feuerstein, 1976) that have shown differential effects of attention on conscious recollection, in comparison with other uses of memory. Dividing attention influenced people's ability to consciously recollect having read a name, as measured by list recognition, but left in place effects of reading a name on its familiarity, as indexed by fame judgments.…”
Section: Discussionsupporting
confidence: 67%
“…When sufficient care is taken to ensure that items are truly unattended, little or no evidence of memory is found on a recognition memory test or a recall test (Fisk & Schneider, 1984;Moray, 1959), which leads to the claim that attention is necessary for memory. However, Eich (1984) found evidence of memory after divided attention by using a test that did not require conscious recollection. Homophones were presented to the unattended channel in a dichotic-listening task, accompanied by a word that biased the homophone to its less common interpretation (e.g., taxi-fare).…”
mentioning
confidence: 99%
“…For the study phase, the 32 homo phones used by Eich (1984) the targets and distractors in each block all had bee n on the spelling test or unspelled, depending on which spelling list the subject had heard. Spelled and unspelled homophones rotated across the four blocks.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated priming effects in amnesic patients who lack explicit memory for study list items (Graf et al, 1984;Squire et al. 1985) and in normal subjects who perform extremely poorly on explicit tests following degraded encoding conditions (Eich, 1984;Jacoby et al,, 1989;Kunst-Wifson & Zajonc, 1980). The present results extend these findings by providing a demonstration of priming in test-unaware normal subjects following both semantic and nonsemantic study conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Eich (1984) presented subjects with a list of nonattended target words and then tested the subjects with both implicit (homophone spelling) and explicit (yes/'no recognition) memory tests. Priming was observed under these study conditions, even though explicit memory for the nonattended target words was at chance level, thereby suggesting that subjects were test unaware during performance of the implicit test.…”
mentioning
confidence: 99%